Proceedings of the 2015 ACM SIGCHI Conference on Creativity and Cognition 2015
DOI: 10.1145/2757226.2764548
|View full text |Cite
|
Sign up to set email alerts
|

"I could play here for hours.." (thinks the visitor and leaves)

Abstract: This paper examines factors that influence how long audience members actively engage with an interactive installation in public settings. The study draws on data from three field studies of an interactive multi-person installation, encompassing questionnaires,video recordings and user-system interaction data. The studies were conducted with unsolicited exhibition audiences during public exhibitions in the UK, China and Spain. In all three studies it was found that the time participants spent interacting with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is also natural for participants to transition from a higher level to a lower level of interaction as they cease interacting with the installation for various reasons. Previous work has found that social factors such as an "obligation to leave" play a large role in causing disengagement with public interfaces [3].…”
Section: Backwards Transitions Backgroundmentioning
confidence: 99%
“…It is also natural for participants to transition from a higher level to a lower level of interaction as they cease interacting with the installation for various reasons. Previous work has found that social factors such as an "obligation to leave" play a large role in causing disengagement with public interfaces [3].…”
Section: Backwards Transitions Backgroundmentioning
confidence: 99%
“…Interactions in these settings tend to be casual, unstructured, walk-up-and-use, dynamic, and fastpaced, as described in an emerging corpus of studies done in real-world settings, often referred to in-the-wild studies (e.g. Bengler and Bryan-Kinns (2015); D'Angelo et al (2015); Hinrichs and Carpendale (2011); Hornecker and Stifter (2006); Marshall et al (2011a)). However, despite some discussion of tensions between strangers trying to use a tabletop application at the same time (Marshall et al, 2011a), there is a paucity of detailed analysis of how groups share access to these technologies and manage transitions of use.…”
Section: Introductionmentioning
confidence: 99%